A comparison of combination of recombinant gonadotrophin and clomiphene citrate protocol with recombinant gonadotrophin alone protocol as ovarian hyperstimulation agents in intrauterine insemination cycles in Hospital Sultanah Nur Zahirah: a pilot study - Nik Hassan, Nik Azi Azuha (2015)

(untitled)
OBJECTIVE: A study was performed in Hospital Sultanah Nur Zahirah to evaluate the efficacy of two minimal ovarian hyperstimulation (MOH) protocols between a combination of clomiphene citrate and recombinant gonadotrophin and recombinant gonadotrophin alone in controlled ovarian hyperstimulation for intrauterine insemination (COH-IUI). METHOD: A prospective randomized controlled trial was conducted at the Infertility Centre of Hospital Sultanah Nur Zahirah for one year duration from 1st October 2013 until 30th September 2014, aged between 24 to 44 years old women, undergoing their first COH-IUI cycle with MOH protocols. 68 women were randomly assigned to each protocol, with 34 women received CC-rFSH protocol and 34 women with rFSH alone protocol. The primary outcomes were to compare the effectiveness of both protocols in term of pregnancy rate and follicle development in term of number and sizes of dominant follicles. In addition, the endometrial thickness in response to each protocol and the incidence of complications related to COH-IUI such as miscarriage, multiple pregnancy and OHSS were also evaluated. RESULT: There were no statistical differences noted between CC-rFSH protocol and rFSH alone protocol in term of sociodemographic, anthropometrics, duration, cause and type of infertility and also sperm counts, motility and morphology, suggestive that the subjects were homogenously distributed. The endometrial thickness of CC-rFSH protocol was 8.5mm, whereas in rFSH alone protocol was 10.1mm. The difference was statistically significant with p value of <0.05. The difference of mean number of follicles was not significant between the two protocol, with 1.79 in CC-rFSH protocol and 1.44 in rFSH alone protocol. The pregnancy rate between the two protocols was not statistically significant with 11.8% versus 8.8% (p value=0.690). There were no cases of higher order pregnancy and no reported incidences of OHSS. There was only 1 case of first trimester miscarriage, but statistically did not achieve any significant difference between the protocols. CONCLUSION: Both minimal ovarian hyperstimulation protocols are equally effective for COH-IUI in term of pregnancy rate with lower incidence of complications. Adoption of both protocols is recommended, and the choice of protocol should be individualised and uniquely chosen to each couple with different causative factor for infertility.